A new contribution to the classification of stressors affecting nursing professionals - Jesús Cremades Puerto; Loreto Maciá Soler; Maria José López Montesinos; Azucena Pedraz Marcos; Víctor Manuel González Chorda
Objective: to identify and classify the most important occupational stressors affecting nursing professionals in the medical units within a hospital. Method: quantitative-qualitative, descriptive and prospective study performed with Delphi technique in the medical units of a general university hospital, with a sample of 30 nursing professionals. Results: the stressors were work overload, frequent interruptions in the accomplishment of their tasks, night working, simultaneity of performing different tasks, not having enough time to give emotional support to the patient or lack of time for some patients who need it, among others. Conclusion: the most consensual stressors were ranked as work overload, frequent interruptions in the accomplishment of their tasks, night working and, finally, simultaneity of performing different tasks. These results can be used as a tool in the clinical management of hospital units, aiming to improve the quality of life of nursing professionals, organizational models and, in addition, continuous improvement in clinical treatment.